HARMONISASI PERAN PELAKU PENDIDlKAN SEBAGAI UPAYA UNTUK MENGOPTIMALISASlKAN FUNGSI PENDIDlKAN - Bambang Syaeful Hadi (LPMPP Universitas Negeri Yogyakarta, 2007)
While education has broad and complex dimensions with eachhaving its own problems, the problem-solving should becomprehensive. A disorder in the Indonesian educational world hasbeen caused by, among others, a disharmony among the roles of theagents of education (i.e., the family, society, and school). Eachperforms with no coordination with any other of the agents. Theresult is that the education has not produced human individuals whoare intellectually, socially, and religiously mature. Rather,oppositely, it has become counterproductive. A segregation of theroles has to be mapped clearly to avoid role overlaps which canmake some important roles left unperformed.The school, as a formal educational institution, is ideally theinstrument enabling the maturation of students' intellectuality, theirmoral attitudes and behaviors, and their contextual skills so thatwhat they obtain from school could be implemented in the societywhere they live. Society, as the environment where studentsassociate with others, is ideally to give them enough room of trust inthe course of motivating them for self-actualization, to restrain fromdemanding too much of them, to take part in monitoring andevaluating them, and to give material and non-material support. Thefamily is a very central place for students' education, where certainother family members become role models and influence theirpsychological growth. The family condition becomes a determiningfactor of the success in their education at school and in society